Peran Kepatuhan Pasien Diabetes Melitus terhadap Terapi Obat dalam Mencegah Komplikasi Penyakit - Aziz, Abdul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Diabetes mellitus is a chronic disease that requires long-term management through pharmacological therapy to control blood glucose levels and prevent complications. The success of drug therapy in patients with diabetes mellitus is strongly influenced by the level of patient adherence to treatment as recommended by healthcare professionals. This article aims to examine the role of patient adherence to pharmacological therapy in preventing complications of diabetes mellitus. The writing method used is a literature review by analyzing various relevant sources, including textbooks and scientific articles related to diabetes mellitus and treatment adherence. The results of the review indicate that patient adherence in taking medication regularly, at the correct dosage, and according to the prescribed schedule plays a crucial role in maintaining stable blood glucose levels and reducing the risk of microvascular and macrovascular complications. In addition, patient knowledge, family support, and the role of healthcare providers significantly influence adherence levels. Therefore, improving patient adherence to pharmacological therapy should be a primary focus in diabetes mellitus management to prevent complications and enhance patients’ quality of life